If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + -5 = 7b Reorder the terms: -5 + 5b = 7b Solving -5 + 5b = 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. -5 + 5b + -7b = 7b + -7b Combine like terms: 5b + -7b = -2b -5 + -2b = 7b + -7b Combine like terms: 7b + -7b = 0 -5 + -2b = 0 Add '5' to each side of the equation. -5 + 5 + -2b = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2b = 0 + 5 -2b = 0 + 5 Combine like terms: 0 + 5 = 5 -2b = 5 Divide each side by '-2'. b = -2.5 Simplifying b = -2.5
| y=-(x+9)2-15 | | 5(x+7)=10x+20 | | C=320+5+3 | | 50=2(2x-5) | | 1898-160= | | 2x-2(x+3)=-6 | | 1898-120= | | 4a+27=9a+8 | | (X+5)(x-5)=90 | | 3/5x-y=52 | | 17=x-2 | | 30b+30m=16b+44m | | -3-3=6 | | 4-1+2x+2x-3=5x+4 | | 12n-6=4n-10 | | 217=81-v | | 3x-cos(6x)=0 | | 535+.21x=585+.13x | | (2D/7)*T=D/2-(D/4)*T | | 13x^2+8x-399=0 | | y=2x^2-6x+11 | | 0.04x^2+8.3x+4.3=0 | | (12+6)=216 | | y=3bz-7x | | 50=8+30x | | 5X+5=2X+3 | | 2(-3-7)+3(x-1)=-4(x-1)-3 | | (2x+1)(-x+3)=0 | | 6x-10=4x+24 | | .5a-3=7-.25a | | 6x+2y+3xy+2+3x+4y-xy= | | -10y=2(3+y) |